Knowledge towards COVID-19 among Medical and Non-Medical Graduates and Postgraduates of Telangana State-A Questionnaire Study (Global Journal of Medical Research, 2021)
Coronavirus disease (COVID-19) is a public health emergency of international concern. Due to its alarming spread across the globe, many countries have imposed drastic lockdown. To mitigate the overburdening of the country's health system, public knowledge regarding the effective control measures towards COVID-19 and their ability to delineate right information from the prevailing myths/misinformation plays pivotal role. Hence the present cross-sectional study is undertaken to assess the knowledge of non-medical and medical, graduates and postgraduates of Telangana state. 17 questions evaluating demographic variables, knowledge and awareness towards COVID-19 were included in the questionnaire and circulated through the electronic mode. Data was collected from 504 participants and their Knowledge score was assessed and statistically analysed. The knowledge of Postgraduates is higher than the graduates and the knowledge of participants belonging to Medical field is higher than Non-Medical graduates with P value of
Keywords: COVID-19; graduates; knowledge; medical; non-medical; postgraduates; telangana state